Insights into the modular design of kinase inhibitors and application to Abl and Axl. Issue 1 (15th November 2021) - Phadke, Sameer; Lopez-Barcons, Lluis; Vandecan, Nathalie; Wu, Zhifen; Johnson, Taylor K.; Lachacz, Eric J.; Merajver, Sofia D.; Soellner, Matthew B.
Abstract : Selectivity analysis and biological testing of a matched set of kinase inhibitors led to the identification of potent, selective inhibitors of Abl (wild-type and T315I) and Axl kinases. Abstract : Scaffold hopping is a common strategy for generating kinase inhibitors that bind to the DFG-out inactive conformation. Small structural differences in inhibitor scaffolds can have significant effects on potency and selectivity across the kinome, however, these effects are often not studied in detail. Herein, we outline a design strategy to generate an array of DFG-out conformation inhibitors with three different hinge-binders and two DFG-pocket groups. We studied inhibitor selectivity across a large segment of the kinome and elucidated binding preferences that can be used in scaffold hopping campaigns. Using these analyses, we identified two selective inhibitors that display low nanomolar potency against Axl or wild-type and clinically relevant mutants of Abl.